Address to the University of Notre Dame, May 1, 1969 - McNamara, Robert S. (World Bank, Washington, DC, 2020)
Robert S. McNamara, President of the World Bank Group, notes that Notre Dame has become a catalytic center of creative thought. It does what universities do best: it probes. It probes the present for what is most formative of the future. And it probes the future for what will most enlarge man's freedom and fulfillment. He goes on to discuss the issue of excessive population growth. The problem will not disappear and must be dealt with soon. If not the opportunity to find a rational and humane solution will disappear.